Effect of water availability on the growth and physiological process of durian (Durian zibethinus) - Ismail, Mohd Razi (1991)
An investigation into the effect of water availability was undertaken on young durian (Durio zibethinus) plants clone D24. Three levels of water availability viz. 100% of field capacity were imposed to the plants. Leaf area, shoot and root dry weight were significantly reduced with the reduction in water supply. Reduction in water availability decreased relative water content and stomatal conductance, but CO2 internal concentration was found increase.